Identification of aircraft gas-turbine dynamics using B-splines neural networks - Lopes, J. C. (2013)
This paper describes preliminary results regarding the development of a B-splines neural network model of the fuel feed to shaft-speed dynamics of a twin-shaft gas turbine engine. Data recorded from practical testing of the turbine to a multisine input were employed, and models were identified at different points along the turbine operating curve. B-splines neural networks have been found to be good models of the system, delivering good results especially for long-range predictions.